Pengaruh Fitur Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pengguna Aplikasi OVO - Putri Lestari HB; Samuel Sumantri (Jurnal Informatika Kesatuan, 2023)
The development of technology and information in the current era of globalization is growing rapidly and rapidly. Starting from the social, cultural, educational and economic aspects, technology has been applied as a means of approaching the community in everyday life. With an online-based information system, people can take advantage of gadgets to help activities that will be carried out quickly and easily anytime and anywhere. Indonesian people generally use cash to make transactions. In the economic aspect, it is possible that in the current technological era, many people in making payment transactions already use E-Money or also known as electronic money. The second most downloaded E-Money application by the Indonesian people is the OVO application. The author will explain the effect of Product Features, Service Quality and User Satisfaction from the OVO Application. The purpose of this study was to determine the effect of product features, service quality on Ovo application user satisfaction. This research is a quantitative research method with data collection method using simple random sampling technique using a questionnaire in the form of a google form which is distributed to all samples online. This research uses analytical tools such as Likert scale, validation test, reliability test, classical assumption test, multiple linear regression analysis, T test, F test and coefficient of determination (r2). The results of this study indicate that product features have a positive and significant effect on user satisfaction, then Service Quality has a positive and significant effect on user satisfaction and there is a positive and significant effect on user satisfaction together. Based on the research results, the t-test value, namely the t-count of the independent variable on the dependent variable, is greater than the t-table, which is 1.984 and the significance value is less than 0.05. Keywords: product features, service quality, and user satisfaction